A Survey of Serials Lists in New England Libraries A Preliminary Report - DeBuse, Raymond, Comp.; New England Board of Higher Education, Wellesley, MA. New England Library Information Network ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
In January 1972, the New England Library Information Network (NELINET) conducted a survey of serials lists and the need for further union list coverage in the New England region. The survey was an outgrowth of a meeting of librarians concerned with serials access in the region held at Worcester Polytechnic Institute in December, 1971. On the basis of questions asked at that meeting NELINET developed three separate questionnaire forms (reproduced in Appendix A) which were subsequently sent out to 229 academic libraries, the six state libraries, and three of the larger public libraries in New England. The first form was directed to the serials librarian and contained questions about multiple-copy serials lists, local or union, which included holdings information from his or her library. The second was directed to the ILL librarian and concerned the use of such lists and the need for additional coverage. The last questionnaire was to be filled out by the editor or coordinator of a union list. This report is a summary of the responses obtained from the survey. (Author)
ERIC Note: (0 References).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Libraries; Library Collections; Library Surveys; Periodicals; Public Libraries; Questionnaires; Serials; State Libraries; Union Catalogs; New England Library Information Network; New England